[Letter to Horace Kornegay, Tobacco Institute, from Ernest Pepples, Brown & Williamson Tobacco] - PEPPLES,E (Tufts Archival Research Center, 2007)
Marginalia; Letter to Horace Kornegay, Tobacco Institute, from Ernest Pepples, Brown & Williamson Tobacco. Requests discussion of the California program. Discusses efforts to avoid the confrontation between smokers' health and nonsmokers' health.